RUKYATUL HILAL INSTRUMENT DESIGN BASED ON ARDUINO - Fajrullah Fajrullah; Zikrullah Hadi; Andi Evan Nisastra (Fakultas Syari'ah dan Hukum UIN Walisongo, 2022)
Arduino is a Microcontroller platform consisting of a computer chip that is used to control electronic equipment that is flexible and easy to use. In this modern era, the implementation of Rukyatul Hilal can be done using instruments such as Hilal locater, telescope and theodolite. However, these tools are quite expensive and have a fairly heavy load and require long time to prepare. Therefore, this research provides breakthroughs and new innovations in designing the Rukyatul Hilal Instrument based on Arduino. The research uses the Research and Development model type of research, the development model that the researcher will do is to develop an Arduino Microcontroller so that it can be used as a Rukyatul Hilal Instrument. Based on 4 observations of the Moon, The Arduino-based Rukyatul Hilal instrument can successfully show the position of the Moon and verify the data used by the author is correct and the author can also photograph the image of the Moon clearly using a smartphone. However, it should be noted that the position of the Moon when viewed from the Arduino-based Rukyatul Hilal Instrument telescope is not in the middle of the telescope, but sometimes at the bottom, side and top.